Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Đặt \(f_{\left(x\right)}=0\)
\(\Leftrightarrow x^3+3x^2-2x-2=0\)
\(\Leftrightarrow x^3-x^2+4x^2-4x+2x-2=0\)
\(\Leftrightarrow x^2\left(x-1\right)+4x\left(x-1\right)+2\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^2+4x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-1=0\\x^2+4x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=1\\x^2+4x+4-2=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\\left(x+2\right)^2=2\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x+2=\sqrt{2}\\x+2=-\sqrt{2}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=1\\x=\sqrt{2}-2\\x=-\sqrt{2}-2\end{matrix}\right.\)
Vậy: \(S=\left\{1;\sqrt{2}-2;-\sqrt{2}-2\right\}\)
b) Đặt \(G_{\left(x\right)}=0\)
\(\Leftrightarrow3x+1=0\)
\(\Leftrightarrow3x=-1\)
hay \(x=\frac{-1}{3}\)
Vậy: \(S=\left\{-\frac{1}{3}\right\}\)
c) Đặt \(A_{\left(x\right)}=0\)
\(\Leftrightarrow2x^2-4=0\)
\(\Leftrightarrow2x^2=4\)
\(\Leftrightarrow x^2=2\)
\(\Leftrightarrow x=\pm\sqrt{2}\)
Vậy: \(S=\left\{\sqrt{2};-\sqrt{2}\right\}\)
d) Đặt \(h_{\left(x\right)}=0\)
\(\Leftrightarrow2x^2+3x-5=0\)
\(\Leftrightarrow2x^2+5x-2x-5=0\)
\(\Leftrightarrow x\left(2x+5\right)-\left(2x+5\right)=0\)
\(\Leftrightarrow\left(2x+5\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2x+5=0\\x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=-5\\x=1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\frac{-5}{2}\\x=1\end{matrix}\right.\)
Vậy: \(S=\left\{\frac{-5}{2};1\right\}\)
e) Đặt P=0
\(\Leftrightarrow3x^2+4x^2+6x+3=0\)
\(\Leftrightarrow7x^2+6x+3=0\)
\(\Leftrightarrow7\left(x^2+\frac{6}{7}x+\frac{3}{7}\right)=0\)
mà 7>0
nên \(x^2+\frac{6}{7}x+\frac{3}{7}=0\)
\(\Leftrightarrow x^2+2\cdot x\cdot\frac{6}{14}+\frac{9}{49}+\frac{12}{49}=0\)
\(\Leftrightarrow\left(x+\frac{3}{7}\right)^2=-\frac{12}{49}\)(vô lý)
Vậy: S=∅
x+y=3 => y=3-x
P=6x2+7x(3-x)+(3-x)2+15(3-x)
P=6x2+21x-7x2+9-6x+x2+45-15x
P=(6x2-7x2+x2)+(21x-6x-15x)+(9+45)
=> P = 54
Đáp số: P=54
20xy - 5y2 + 3xy - 6x2
= (20xy + 3xy) - 5y2 - 6x2
= 23xy - 5y2 - 6x2